Inducible nitric oxide synthase: Good or bad? - Lind, Maggie; Hayes, Alan; Caprnda, Martin; Petrovic, Daniel; Rodrigo, Luis; Kruzliak, Peter; Zulli, Anthony (Biomedicine & pharmacotherapy, 2017)
Nitric oxide synthases (NOS) are a family of isoforms responsible for the synthesis of the potent dilator nitric oxide (NO). Expression of inducible NOS (iNOS) occurs in conditions of inflammation, and produces large amounts of NO. In pathological conditions iNOS is regarded as a harmful enzyme and is proposed to be a major contributor to diseases of the cardiovascular system such as atherosclerosis. In this review, we address the notion that iNOS is a detrimental enzyme in disease and discuss its potentially beneficial roles. Additionally, we describe other molecules associated with iNOS in diseases such as atherosclerosis, and current research on therapeutic inhibitors tested to reduced pathology associated with cardiovascular diseases (CVD).
Keywords: Nitric Oxide Synthase; lidé; Nitric Oxide Synthase Type II; Nitric oxide synthase (NOS); Cardiovascular Diseases; synthasa oxidu dusnatého; Cyclooxygenase-2 (COX-2); zvířata; Humans; oxid dusnatý; Endothelial NOS (eNOS); Nitric Oxide; Cardiovascular diseases; Inducible NOS (iNOS); COX-2; kardiovaskulární nemoci; Oxidative stress; synthasa oxidu dusnatého, typ II; Animals